1995
DOI: 10.1007/bf00311536
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hypothermic preservation of cardiac myocytes isolated from the neonatal rat ventricle: A comparison of various crystalloid solutions

Abstract: In this study, the functional and biochemical effects of crystalloid solutions on immature cardiac myocytes incubated under hypothermic conditions were evaluated. Cardiac myocytes were isolated from neonatal rat ventricles and cultured for 4 days, following which 12.5 x 10(5) myocytes per flask were incubated at 4 degrees C for 3, 6, 12, and 18 h in five types of crystalloid solutions: lactated Ringer's (LR), St. Thomas' Hospital (ST), University of Wisconsin (UW), 5% glucose-based potassium (GK), and normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The ability to efficiently cold-preserve functional CMs for extended periods would provide an appealing off-the-shelf solution for the treatment of cardiac diseases. Several studies have evaluated the ability to preserve adult/neonatal rat/mouse CMs at hypothermic conditions [16,[26][27][28][29]. For example, Snyder et al reported the successful hypothermic storage of neonatal rat ventricular CM monolayers for up to 72 hours in HTS.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to efficiently cold-preserve functional CMs for extended periods would provide an appealing off-the-shelf solution for the treatment of cardiac diseases. Several studies have evaluated the ability to preserve adult/neonatal rat/mouse CMs at hypothermic conditions [16,[26][27][28][29]. For example, Snyder et al reported the successful hypothermic storage of neonatal rat ventricular CM monolayers for up to 72 hours in HTS.…”
Section: Introductionmentioning
confidence: 99%
“…For transport of myocardial specimen, most protocols opt for the Thomas solution [ 18 ] or cardioplegic buffer [ 19 , 20 ] as the transport medium. It has been reported that the UW solution showed beneficial effects on the recovery of myocyte viability compared to the Thomas’ Hospital and glucose-based potassium solutions [ 21 ]. Additionally, the superior myocardial protective effects of HTK solution, as compared with conventional St. Thomas crystalloid cardioplegia has been proved [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…18,[28][29][30][31] In order to accomplish this, the neonatal rat ventricular cardiomyocyte (NRVCM) in vitro cardiac model was utilized in combination with cryomapping and ablation thermal stress models. 32,33 The window of temperature exposure included three distinct thermal zones including: hyperthermia (40°C to 60°C), hypothermia (15°C to 2°C), and subfreezing temperatures reaching Ϫ20°C. Exposure intervals of 15 sec to 60 sec were employed to evaluate the temporal effects at the various temperatures.…”
Section: Introductionmentioning
confidence: 99%